Some Aspects of Schoolchild’s and Students’ Ethnic Identity Development Though Ethnic Instrumental Music - Palubinskienė, Vida (Pedagogika, 2015)
One of the basic objectives of contemporary pedagogy is developing youth’s national musical culture. In the course of history, when the idea of Lithuanian independence used to become realistic and tangible, special attention was paid to identity issues. The efforts to sustain and to thoroughly foster our traditions, customs, language and ethnical music had the greatest impact on the development of Lithuanian people’s national awareness. The essential categories characterizing the Lithuanian national identity have been and remained self-awareness, language, customs, folk art, and ethnical instruments. Playing instrumental music in ensembles using ethnical instruments has also greatly contributed to preserving of Lithuanian traditions and national identity, as a way of national awareness. Object of research: Some aspects of schoolchild’s and students ethnic identity development through ethnic instrumental music. Aim of research: investigate of the meaning of teaching ethnic instrumental music in the process of developing the knowledge of the ethnical identity. Methods of research: questionnaire scientific methodological literature review, questionnaire and a summary of comparison. The traditions of playing instrumental music in ensembles are quite old and deep-rooted in Lithuania. Ethnical instruments (the kanklės, reed-pipes, pan flutes, etc.) have been always regarded as a symbol of national awareness. Therefore, continuity and dissemination of related traditions and their application in various aspects contributes, at least partially, to the possibility of preserving national values and developing national identity. Playing instruments in ensembles helps young people develop their musical listening skills and memory, get more matured spiritually, as well as form aesthetic feelings and artistic understanding of music. For educators, the ability to play different ethnical instruments is helpful in the respect of having more variety in their classes, involving the learners in extracurricular activities, and making closer acquaintances with the pupils and their parents. The possibility to develop the national identity of young people by means of playing in ensembles is exploited not only in Lithuania. This kind of experience has been used quite long in the practices of other countries. Therefore, in the rapid course of globalisation processes, it is of great importance to educate the young generation in the spirit of national traditions.